Escolas do campo e atendimento educacional especializado em sala de recursos multifuncional - Palma, Debora Teresa [UNESP] (2016)
Special education in the inclusive perspective has been discussed in several researches. However, there are few articles that treat disabled people who live and study in the country. Because of this, the aim of this research was to analyze the Specialized Education Attendance (SEA) developed in the country schools. The research followed a qualitative approach and had as a methodological procedure the Case Study. For data obtaining, questionnaires were used as well as observation, photographic register and analysis of school documents. The research was performed in three country schools located in an inner city of São Paulo state with thirty-one teachers of regular teaching. From these, seventeen were responsible by the students met by the SEA service, and the researcher, given that the Special Education Teacher is active in the Multifunctional Resources Classroom of the selected schools.The results of the observation revealed that only one school has adequate space for the functioning of the Multifunctional Resources Classroom. The kind of deficiency found in all three schools is the intelectual, and the organization of one Special Education teacher to attend the three units is not enough. In addition, it was identified that these students take part of the SEA in the same school shift due to the transportation difficulty, diverging of the proposal established in legislation. The data analyzed from the teachers' questionnaire point out the attitudinal change of the teachers in considering the disabled students as public of regular teaching and they also reinforce the little contact for orientation with the expert teacher. Finally, the results of the familiar questionnaire point out that the family does not see their children's difficulties as a deficiency. It is hoped that this study can subsidize the debate for the construction of public politics that consider the particularities of the disabled people who live and study in the country.